1996
DOI: 10.1046/j.1365-2567.1996.d01-685.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation by mitogens and superantigens of axolotl lymphocytes: functional characterization and ontogenic study

Abstract: SUMMARYUrodele amphibians have weak and slow immune responses compared to mammals and anuran amphibians. Using new culture conditions, we tested the ability of lymphocytes of a well-studied salamander, the Mexican axolotl (Ambystoma mexicanum) to proliferate in vitro with diverse mitogenic agents. We demonstrated that the axolotl has a population of B lymphocytes that proliferate specifically and with a high stimulation index to the lipopolysaccharide (LPS) known as a B-cell mitogen in mammals. This proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…These studies showed that the response in these species occurs between one to thirty days after treatment. Similar responses could be also present in other amphibian groups as it was found that LPS from Escherichia coli 026:B5 activated the production of B lymphocytes of the urodele axolotl A. mexicanus in vitro after three day treatments (Salvadori and Tournefier, 1996) indicating its in vivo potential. However, up to now, in vivo effects of LPS have not been studied in any urodele species.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…These studies showed that the response in these species occurs between one to thirty days after treatment. Similar responses could be also present in other amphibian groups as it was found that LPS from Escherichia coli 026:B5 activated the production of B lymphocytes of the urodele axolotl A. mexicanus in vitro after three day treatments (Salvadori and Tournefier, 1996) indicating its in vivo potential. However, up to now, in vivo effects of LPS have not been studied in any urodele species.…”
Section: Introductionsupporting
confidence: 75%
“…At this stage it is not possible to completely rule out the possible interactions of the LPS with the host immune cells. Furthermore, due to the observed effects of the LPS on stimulation of B lymphocytes of the axolotl (Salvadori and Tournefier, 1996), we could still expect that the LPS injection yield the similar immune activation in other newt species as in frogs, despite the absence of its obvious effects on sexual traits of males of L. helveticus. Generally, such a non-activation would be surprising given that (i) LPS is a firmly established immune elicitor which has been shown to efficiently activate the immune system in a large range of taxa including insects, birds, mammals, reptiles and anuran amphibians, and (ii) LPS stimulates both innate and acquired immunity, which both are phylogenetically highly conservative in vertebrates, despite a few particularities (Chen and Robert, 2011;Rollins-Smith and Woodhams, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Low allelic polymorphism has been noticed in the axolotl at the protein level by isoelectric focusing analysis of class II immunoprecipitates [12,25]. Yet, despite their ability to bind superantigens [26], a limited set of antigenic peptides would be presented by axolotl class II molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Urodele amphibians have weak and sluggish immune responses compared to mammals and anuran amphibians. Using a new culture medium ( Salvadori and Tournefier, 1996 ) supplemented with 20 mM 2-ME in place of Leibovitz L-15 medium, lymphocytes of a salamander, the Mexican axolotl ( Ambystoma mexicanum ) were stimulated to proliferate in vitro by the lymphoid mitogens, lipopolysaccharide (LPS), phytohaemagglutinin (PHA), concanavalin A (Con A), and two superantigens, staphylococcal enterotoxins A and B (SEA and SEB). LPS induced B-cells to proliferate and produce antibodies similarly throughout ontogenesis.…”
Section: Resultsmentioning
confidence: 99%